Influence of residual stress profile and surface microstructure on fatigue life of a 15-5PH. (2018) - Valiorgue, F.; Zmelty, V.; Dumas, M.; Chomienne, V.; Verdu, C.; Lefebvre, F.; Rech, J.
Abstract: This works aims at identifying the influence of surface integrity parameters on fatigue life of a 15-5PH. The effect of residual stress profile, surface roughness and microstructure are investigated. Various cutting and superfinishing processes (turning, ball burnishing and belt finishing) are used so as to reach various engineered surface integrities and as a consequence to highlight the influence of each surface integrity parameter. Rotary-bending tests have been carried out on samples to determine the average fatigue strength at 2 million cycles. It is shown that the influence of a deep compressive sublayer is by far more important than the ones of surface roughness or microstructure. The so-called 'white-layer' brings also a slight improvement of fatigue resistance.